John Duns Scotus as precursor of the concept of intuition - Surzyn, Jacek (Folia Philosophica, 2012)
Review of Grzegorz W. Salamon's book: The Concept of Intuitive Cognition in John Duns Scotus. Niepokalanów 2007.